Observations on the isolation of Streptococcus equi from polluted material (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1955)
Using "SF Medium (Difco B 315)" and working with 209 samples of material from equines' nostrils the A. wonder at the negative results showed in relation to St. equi and St. zooepidemicus. Then using three liquid media — "SF Medium", "Lacerda & Freitas" medium and glucose broth — made comparative tests with 193 new samples of the same nature.Due to the circumstances of better results were showed when working with “Lacerda and Freitas” medium, the A. suggests that the not favorable behavior of "SF Medium" is tied to the fast change of the pH. It seems to the A. that these findings are induced by the growing up of viridans group streptococci which are normaly present in equines' nostrils and whose luxurious growing up in such medium is very well known.